Clausal-Internal Scrambling in Urdu Language: A Derivation by Phases - Ali, Asad; Jabbar, Qaisar; Kiani, Humayun (The Institute of Research and Community Service (LPPM) - Universitas Lancang Kuning, 2021)
Scrambling in Clausal-Internal is accounted for employing minimalist program as a theoretical framework on Urdu Naturalistic data in this study. For empirical evidence, an Urdu corpus has been accumulated in audio-recording forms from 100 competent Urdu speakers within the natural setting, taking Naturalist Inquiry as methodological purposes. Employing minimalist program on Urdu data, this study vehemently postulates that the dislocation of arguments from base to host position only hinges on the phase heads— Co and vo; hence no other external devices essentially necessitate accounting for scrambling. This study highlighted scrambling in clausal-internal specifically within Indo-Aryan Languages is Universal Phase-Based parsimony, and it is only controlled by the exiting mechanism within the phase theory. Moreover, the only merge and move operations linearize the CP in a phase-based fashion while CP is a higher phase and vP is a lower phase. No additional AGRoP necessitates scrambling, but one phase successively and cyclically converges into a higher phase level, i.e. CP and the derivation matches at LF and PF interfaces satisfying Full Interpretation (FI).